EFEKTIVITAS MEDIA GAME EDUKASI WORDWALL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Yessyka Fitrian Hardiana; Ina Agustin; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital revolution in education demands learning innovations that can adapt to the characteristics of the digital generation of students. This study analyses the impact of implementing the educational game platform Wordwall on the academic achievement of primary school students. The study was conducted using a descriptive quantitative approach with 16 fifth-grade students at UPT SDN Bejagung 2 Tuban as the research subjects. Data collection was conducted through pre- and post-intervention evaluations using test instruments. The effectiveness analysis used the N-Gain formula to measure changes in students' understanding before and after the use of the digital media. The findings showed significant progress in learning outcomes, with the average score increasing from 58 points to 83 points. The N-Gain calculation yielded a value of 64%, categorising this media as ‘moderately effective’ in supporting the learning process. The most notable transformation was observed in the aspect of learning completion, where the majority of participants (92%) achieved the minimum standards set after using this platform. The research results confirm that educational game technology can be a beneficial learning tool for enhancing student engagement and academic performance in primary schools, although further optimisation is still needed to achieve maximum effectiveness.